Different pro-angiogenic potential of γ-irradiated PBMC-derived secretome and its subfractions. Issue 1 (December 2018) - Wagner, Tanja; Traxler, Denise; Simader, Elisabeth; Beer, Lucian; Narzt, Marie-Sophie; Gruber, Florian; Madlener, Sibylle; Laggner, Maria; Erb, Michael; Vorstandlechner, Vera; Gugerell, Alfred; Radtke, Christine; et al.
Abstract Secretomes from various cell sources exert strong regenerative activities on numerous organs, including the skin. Although secretomes consist of many diverse components, a growing body of evidence suggests that small extracellular vesicles (EVs) account for their regenerative capacity. We previously demonstrated that the secretome of γ-irradiated peripheral blood mononuclear cells (PBMCs) exhibits wound healing capacity. Therefore, we sought to dissect the molecular composition of EVs present in the secretome and compared wound healing-related activities of these EVs to other subfractions of the secretome and the fully supplemented secretome (MNCaposec ). Compared to EVs derived from non-irradiated PBMCs, γ-irradiation significantly increased the size and number and changed the composition of released EVs. Detailed characterization of the molecular components of EVs, i.e . miRNA, proteins, and lipids, derived from irradiated PBMCs revealed a strong association with regenerative processes. Reporter gene assays and aortic ring sprouting assays revealed diminished activity of the subfractions compared to MNCaposec . In addition, we showed that MNCaposec accelerated wound closure in a diabetic mouse model. Taken together, our results suggest that secretome-based wound healing represents a promising new therapeutic avenue, and strongly recommend using the complete secretome instead of purified subfractions, such as EVs, to exploit its full regenerative capacity.